ANTIOXIDANT POTENTIAL OF INDIAN GOOSEBERRY (Emblica officinalis) AQUEOUS EXTRACT IN CHICKEN MEAT BALLS - R. Abinayaselvi; D. Santhi; A. Kalaikannan; A. Natarajan; K. Rajendran (Indian Journal of Veterinary and Animal Sciences Research, 2025)
This study was conducted to evaluate the antioxidant potential of Indian gooseberry (Emblica officinalis) aqueous extract in chicken meat balls and the assessment of the physico-chemical and sensory properties of the meat balls. Chicken meat balls were prepared with the inclusion of Indian gooseberry aqueous extract (GBAE) at 0, 9%, 12% and 15% levels. The emulsion pH, product pH, emulsion stability and product yield were determined. DPPH scavenging activity (%) was studied to establish the antioxidant potential of the GBAE in the product. Sensory properties were evaluated using 8 point hedonic scale. Emulsion pH and product pH decreased significantly (P<0.05) with the addition of GBAE. Product yield decreased significantly (P<0.05) with the addition of GBAE at 12% and 15% levels. DPPH scavenging activity significantly (P<0.01) increased with increase in the GBAE inclusion level, where 15% treatment had the highest antioxidant potential followed by 12% and 9% treatments. The sensory scores of control and 9% treatment were comparable and the scores were significantly (P<0.05) lower for 12% and 15% treatments. From this study, it is observed that GBAE could be added as a potential antioxidant in the chicken meat balls, up to a level of 9% without affecting the physico-chemical and sensory qualities of the product.